The Influence of Environmental Costs, Implementation of Good Corporate Governance and Current Ratio on the Financial Performance of Industrial Companies Listed on the Bei For the 2020-2023 Period - Fernando Bagas Pratama; Sunita Dasman (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research analyzes the influence of environmental costs, implementation of good corporate governance (GCG), and current ratio on the financial performance of industrial companies listed on the IDX for the 2020-2023 period. Independent variables include environmental costs, institutional ownership, managerial ownership, and current ratio, while financial performance is measured by Return on Assets (ROA). The results of the analysis show that environmental costs and current ratio have a positive and significant effect on financial performance. On the other hand, institutional ownership and managerial ownership as indicators of GCG do not have a significant effect. These findings underscore the importance of environmental and liquidity management in improving corporate financial performance.